The kinematics and kinetics of riding a racehorse: A quantitative comparison of a training simulator and real horses. Issue 14 (3rd October 2016) - Walker, A.M.; Applegate, C.; Pfau, T.; Sparkes, E.L.; Wilson, A.M.; Witte, T.H.
Abstract: Movement of a racehorse simulator differs to that of a real horse, but the effects of these differences on jockey technique have not been evaluated. We quantified and compared the kinematics and kinetics of jockeys during gallop riding on a simulator and real horses. Inertial measurement units were attached mid-shaft to the long bones of six jockeys and the sacrum of the horse or simulator. Instrumented stirrups were used to measure force. Data were collected during galloping on a synthetic gallop or while riding a racehorse simulator. Jockey kinematics varied more on a real horse compared to the simulator. Greater than double the peak stirrup force was recorded during gallop on real horses compared to the simulator. On the simulator stirrup forces were symmetrical, whereas on a real horse peak forces were higher on the opposite side to the lead limb. Asymmetric forces and lateral movement of the horse and jockey occurs away from the side of the lead leg, likely a result of horse trunk roll. Jockeys maintained a more upright trunk position on a real horse compared to simulator, with no change in pitch. The feet move in phase with the horse and simulator exhibiting similar magnitude displacements in all directions. In contrast the pelvis was in phase with the horse and simulator in the dorso-ventral and medio-lateral axes while a phase shift of 180° was seen in the cranio-caudal direction indicating an inverted pendulum action of the jockey.